2020
DOI: 10.1097/mnm.0000000000001220
|View full text |Cite
|
Sign up to set email alerts
|

Molecular subtypes of invasive breast cancer: correlation between PET/computed tomography and MRI findings

Abstract: Objective The aim of the study was to investigate the diagnostic value of fluorodeoxyglucose-18 (FDG)-PET/computed tomography (CT) and MRI parameters in determining the molecular subtypes of invasive breast cancer. Methods Data from 55 primary invasive breast cancer masses in 51 female patients who underwent pre-treatment PET/CT and MRI scans, and histopathological diagnosis at the authors’ center were retrospectively reviewed. The relationship between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 21 publications
4
9
0
Order By: Relevance
“…PACS has an important application in tumor diagnosis because of its high spatial and density resolution. In this study, the tumor density was slightly higher than that of the gland on PACS plain scan, and the PACS values were more variable on enhanced scan, which is consistent with previous studies, due to the abnormal metabolism of breast tumor, the varying degree of development, and the high iodine uptake by tumor cells [21].…”
Section: Discussionsupporting
confidence: 92%
“…PACS has an important application in tumor diagnosis because of its high spatial and density resolution. In this study, the tumor density was slightly higher than that of the gland on PACS plain scan, and the PACS values were more variable on enhanced scan, which is consistent with previous studies, due to the abnormal metabolism of breast tumor, the varying degree of development, and the high iodine uptake by tumor cells [21].…”
Section: Discussionsupporting
confidence: 92%
“…PET and MRI represent the most promising imaging modalities for this purpose, due to their ability to non-invasively inform on cancer metabolism, cellularity, and neoangiogenesis. Such properties are reported to be different between BC subtypes which exhibit different biological aggressiveness and behavior [ 32 ]. TNBC is characterized by higher glucose metabolism, which is reflected in its higher SUV values compared with other BC subtypes as seen in other studies [ 32 , 33 ] as well as in this investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Such properties are reported to be different between BC subtypes which exhibit different biological aggressiveness and behavior [ 32 ]. TNBC is characterized by higher glucose metabolism, which is reflected in its higher SUV values compared with other BC subtypes as seen in other studies [ 32 , 33 ] as well as in this investigation. However, quantitative parameters (e.g., DWI-ADC values) alone do not seem to be accurate enough to discriminate molecular BC subtype; thus, more sophisticated AI-enhanced approaches are necessary [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“… 41 Recently, Akin et al investigated how accurately PET-CT scan and MRI could detect breast cancer subtypes in 55 tumors. 136 They found that although the SUVmax value from PET-CT scan was high for the Luminal A subtype, it was lower than the SUVmax value of the other breast cancer subtypes. PET-CT scan was better at identifying the molecular subtype of the breast cancer; however, MRI was superior at determining the tumor size, thus better for staging.…”
Section: Lymphovascular Invasion and Lymph Node Involvementmentioning
confidence: 97%